Histomorphological Spectrum and Trend of Spinal Neoplastic Lesions: A Single Institutional 40-year review (2021)
Objectives: Spinal tumors are much less common compared to brain neoplasms. In our setting, due to poor data collection, underreporting, and limited presentation to medical facilities, studies on spinal tumors are sparse. Consequently, there is a lack of data on the frequency of spinal tumors in a predominantly Black population. Previous studies in our environment reported spinal tumors to be infrequent, with extramedullary tumors being more common. This study examines the histomorphological spectrum of spinal tumors in an African setting, comparing it with previous observations to determine possible changes over the decades. Methods: Data were obtained from hospital records of patients over a forty-year period. Information collected included patients’ age, gender, and histomorphological data of all neoplastic spinal lesions. The data were analyzed using SPSS version 20 statistical software. Results: Tumors were more common between the third and sixth decades of life. There was a slight male preponderance, with a male-to-female ratio of 1.2:1. Meningiomas were the most common tumors seen during the study period, contrasting with previous studies that had shown Burkitt lymphoma as predominant. The data also showed a steady rise in the number of cases over the study period, suggesting increased hospital presentations and more surgical interventions. Conclusion: This study showed differences in patient demographics and histological tumor types compared to previous reports. These changes are likely due to better awareness among patients and improved diagnostic facilities.